Through the Iron Bars: Reason, Relationship, and Realm in Western - Phuyal, Komal Prasad (Bagiswori Journal, 2026)
Western modernity heavily relies on rationalization to achieve social maturity, in which people experience similar experiences and engage in indirect social relationships. Extensively surveying the critical debate of Western modernity in which thinkers like Immanuel Kant (1724-1804), Michel Foucault (1926-1984), and Jürgen Habermas (1929-2026) have actively participated and critically contributed to the understanding of modernity through social and political analysis of the Western experience. This paper argues that modernity functions iron bars enforcing limits to the use of reason, social relationship, and the realm of freedom for a human agent. Through a textual study of the critical debate, this paper explores perceptions of Western modernity, which applies transcendental reasoning to reach a higher level of abstraction and claims that all societies can have the same, ultimate experience. Though later philosophers who argue for the cultural dynamics of modernity reject such claims about Western modernity, this paper limits itself to a discussion of Western modernity and explores homogeneity, rationalization, and indirect social relationships as the key dynamics. Through qualitative study and textual analysis, this paper uncovers the place of reason, human relationship, and the place of agency in the discourses of Western modernity.